Estimation of minimal detectable change in the 10-meter walking test for patients with stroke: a study stratified by gait speed - Hosoi, Yuichiro; Kamimoto, Takayuki; Sakai, Katsuya; Yamada, Masanari; Kawakami, Michiyuki (Frontiers in Neurology, 2023)
Objective This study aimed to classify and calculate the minimal detectable changes (MDC) in gait time and gait speed in a 10-meter walking test (10MWT) in patients with stroke classified according to their gait speed. Methods The participants were 84 patients with stroke. Their gait times were measured twice each at their comfortable gait speed (CGS) and maximum gait speed (MGS) on a 10-meter straight track, and gait speed was calculated using gait time. Participants were assigned to three speed groups based on their CGS: low-speed (<0.4 m/s; n = 19); moderate-speed (0.4–0.8 m/s; n = 29); and high-speed (>0.8 m/s; n = 36). For each group, first and second retest reliability and MDC of CGS and MGS were calculated using gait time and gait speed in the 10MWT. Results MDCs in the 10MWT at CGS were: low-speed group, gait time 5.25 s, gait speed 0.05 m/s; moderate-speed group, gait time 2.83 s, gait speed 0.11 m/s; and high-speed group, gait time 1.58 s, gait speed 0.21 m/s. MDCs in the 10MWT at MGS were: low-speed group, gait time 7.26 s, gait speed 0.04 m/s; moderate-speed group, gait time 2.48 s, gait speed 0.12 m/s; and high-speed group, gait time 1.28 s, gait speed 0.19 m/s. Conclusion Since the MDC of gait speed and gait time differ depending on the participant’s gait speed, it is necessary to interpret the results according to the participant’s gait speed when judging the effectiveness of therapeutic interventions.